## Description

----------------------------------------------------------------------------------------------------

Solve the equation by completing the square.

x2 - 10x + 28 = 0

a. x ≈ 3.3, x ≈ 6.7

b. x = 5 + i√3, x = 5 − i√3

c. x ≈ 18.5, x ≈ 1.5

d. x = 10 + i√3 , x = 10 − i√3

==========================================

Rewrite the equation so that the left side is a factored perfect square.

3x2 - 4x = 2

======================================

Write an equation equivalent to the one below by writing the trinomial as a perfect square trinomial.

x2 + 8x + 9 = - 9

a. x2 + 8x + 16 = 16

b. x2 + 8x + 16 =- 2

c. x2 + 8x + 64 = 46

d. x2 + 8x + 64 = 64

==============================================

Find the value of c that will make the expression a perfect square trinomial.

x2 + 0.6x + c

a. 0.3

b. 0.36

c. 0.9

d. 0.09

==============================================

Write an equation equivalent to the one below by writing the trinomial as a perfect square trinomial.

A. | |

B. | |

C. | |

D. |

================================================

Write an equation equivalent to the one below by writing the trinomial as a perfect square trinomial.

x2 - 4x + 1 = 0

a. x2 - 4x + 4 = -3

b. x2 - 4x + 5 = 0

c. x2 - 4x + 4 = 3

d. x2 - 4x + 4 = 5

======================================

Find the value of c that will make the expression a perfect square trinomial.

x2 - 15x + c

a. -7.5

b. 7.5

c. -56.25

d. 56.25

================================================

Rewrite the equation by factoring the perfect square trinomial.

x2 + 8x + 16 = 7

a. (x + 4)2 = 7

b. (x - 4)2 = 7

c. (x + 8)2 = 7

d. (x - 8)2 = 7

==============================================

Rewrite the equation by factoring the perfect square trinomial.

x2 + 12x + 36 = 25

a. (x - 6)2 = 5

b. (x - 6)2 = 25

c. (x + 6)2 = 25

d. (x + 6)2 = 5

## Explanation & Answer

Hi again,I have double-checked all answers, and they are as follows:BABD...